Cord blood immune profile: Associations with higher prenatal plastic chemical levels. (15th December 2022) - Eisner, Alex; Gao, Yuan; Collier, Fiona; Drummond, Katherine; Thomson, Sarah; Burgner, David; Vuillermin, Peter; Tang, Mimi LK.; Mueller, Jochen; Symeonides, Christos; Saffery, Richard; Ponsonby, Anne-Louise; et al.
Abstract: Prenatal exposure to plastic chemicals has been associated with alterations to early-life immune function in children. However, previous studies have generally been small and focused on limited repertoires of immune indices. In a large population-based pre-birth cohort (n = 1074), third-trimester measurements of eight phthalate metabolites and three analogues of bisphenols were used to estimate prenatal exposure to phthalate and bisphenol compounds. In cord blood, immune cell populations were measured by flow cytometry and an extensive panel of cytokines and chemokines were measured by multiplex immunoassay. We used these cord blood analytes to estimate "early life" immune profiles. The full study sample comprises data from 774 infants with prenatal plastic metabolite measurements and any cord blood immune data. Multiple linear regression analysis was used to evaluate whether prenatal phthalate and bisphenol exposure was prospectively associated with cord blood immune cell populations and cytokine and chemokine levels. Generally, inverse associations were observed between prenatal phthalate exposure and cord blood immune indices. Higher exposure to di-n-butyl phthalate was associated with lower cord blood levels of platelet-derived growth factor (PDGF) and interferon gamma-induced protein 10 (IP-10); higher exposure to the sum of dibutyl phthalates was associated with lower cord blood levels of IP-10; and higher exposure to benzyl butyl phthalate was associated with lower cord blood levels of interleukin 1 beta (IL-1β). There was less evidence of associations between bisphenols and cord blood immune indices. These results extend previous work examining prenatal plastic chemical exposure and early-life immune development and highlight the importance of further examination of potential associations with health-related outcomes. Graphical abstract: Image 1 Highlights: Prenatal phthalate exposure is associated with lower cytokine levels at birth. Exposure to di-n-butyl phthalate is associated with lower PDGF and IP-10 levels. Exposure to the sum of dibutyl phthalates is associated with lower IP-10 levels. Exposure to benzyl butyl phthalate is associated with lower IL-1β levels.